Household Food Insecurity Is Associated with Childhood Asthma. Issue 12 (21st October 2015) - Mangini, Lauren D; Hayward, Mark D; Dong, Yong Quan; Forman, Michele R
Abstract: Background: In 2013, 20% of US households with children experienced food insecurity. Asthma afflicts over 7 million children; prevalence has steadily increased while incidence peaks in young children. Asthma and food insecurity share the determinants of poverty and race that are associated with weight, yet limited research on the relation between food insecurity and asthma exists. Objective: The objective of this study was to determine the association between food insecurity and asthma in a diverse sample of children. Methods: Cross-sectional data from grade 3 of the Early Childhood Longitudinal Study–Kindergarten Cohort were analyzed ( n = 11, 099). Food security based on the USDA module and asthma diagnosis were reported by parents; anthropometric factors were measured. Multivariate logistic regression models of food security and asthma were analyzed overall and by race/ethnicity. Results: Children in food-insecure households had a 4% higher adjusted odds of asthma (95% CI: 1.02, 1.06). Adjusted odds of asthma were also higher by 70% for males (95% CI: 1.69, 1.71), 53% for non-Hispanic black (NHB) children (95% CI: 1.51, 1.54), 20% for Hispanic children (95% CI: 1.19, 1.21), 38% for overweight children (95% CI: 1.36, 1.39), 67% for obese children (95% CI: 1.65, 1.68), 23% for low–birth weight children (95% CI: 1.21, 1.24), 24% if mothers had a high school diploma (95% CI: 1.23, 1.26), and 33% if mothers had some college education (95% CI: 1.32, 1.35). High–birth weight children (OR: 0.84; 95% CI: 0.83, 0.85) and those with foreign-born mothers (OR: 0.52; 95% CI: 0.51, 0.53) had lower odds of asthma. Being food-insecure remained positively associated with asthma in non-Hispanic whites and Hispanics but was inversely associated with odds among NHBs. Odds of asthma doubled (OR: 2.00; 95% CI: 1.97, 2.03) for all children in households that were both food-insecure and poor; this relation remained positive in race/ethnicity-specific models. Conclusions: Food insecurity is positively associated with asthma in US third graders, and household poverty strengthens the association.